The Status of the Arabic Language: Challenges of Decline and Prospects for Advancement from a Political Perspective (The International Journal of Educational Sciences and Arts, 2024)
This study addresses the issue of the declining status of the Arabic language from a political perspective, focusing on the role of political factors in this regression. These factors are examined on two levels: externally, the analysis explores the impact of foreign influence policies and the resulting cultural infiltration in the Arab world; internally, it investigates the political frameworks of Arab regimes that often lack serious political will for cultural and linguistic revitalization, alongside the fragility of the Arab regional system and the shortcomings of educational policies that have contributed to weak language usage.The study concludes that the decline in the status of the Arabic language is attributable to both internal and external political factors. Chief among these are the absence of genuine political will for cultural and linguistic advancement, the lack of cohesion and strength within the Arab regional system, the prevalence of unilateral agreements over integrative diplomacy in Arab relations, and the inadequacy of legislation and laws necessary to regulate language usage effectively.
Keywords: Status of the Arabic Language; Linguistic Decline; Political Factors; Foreign Influence; Cultural Penetration; Arab Regimes; Educational Policies